Pengaruh Intellectual Capital Terhadap Kinerja Keuangan pada Bank Pembiayaan Rakyat Syariah (BPRS) di Indonesia dengan Model Value Added Intellectual Capital (VAIC) Periode 2016-2020 - Daulay, Mahdalena; Puteri, Hesi Eka; Baskara, Reina Tasha; Zai, Jamainida (ITB AAS INDONESIA Surakarta, 2023)
Competition in the Islamic banking industry is tight, so the competence of Islamic banking human resources must increase. This needs to be done to increase the lack of resources who have studied and received good education and training, but when they return due to unfavorable environmental factors, the results of education and research be wasted. This study aims to determine the effect of Intellectual Capital on Financial Performance in Islamic People's Financing Banks (BPRS) in Indonesia with the Value Added Intellectual Capital (VAIC) Model. There is research data using monthly time series data taken in the 2016-2020 period. Data analysis technique uses PLS (Partial Least Square) with processing using Warp-PLS 7.0 Software. The test results using the SEM-PLS approach show that Intellectual capital IB-VACA has a positive and significant effect on the financial performance of Indonesian Islamic banking. By obtaining a path coefficient value of 0.482 with a p value of P